Optimization of the Library on the Learning Outcomes of Qur'an and Hadith for Seventh-Grade Students at MTs in Barru Regency - Ma'ruf; Ahdar; Muzakkir; Mahsyar Idris; Muhammad Jufri (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to examine the optimization of library utilization through digital literacy and its influence on students’ learning outcomes in Al-Qur’an and Hadith among seventh-grade MTs students in Barru Regency. Specifically, the study seeks to analyze the use of the library by seventh-grade students at MTs DDI Takkalasi, Barru Regency, and to investigate the optimization of the library through digital literacy in relation to students’ learning outcomes in Al-Qur’an and Hadith. The research employed an associative quantitative method, allowing data collection in numerical form and statistical analysis to examine the relationship between variables. A causal research approach was used, involving a sample of 133 students. Data were analyzed using simple linear regression with the assistance of SPSS version 24. The results show that the use of the library by seventh-grade students at MTs DDI Takkalasi, Barru Regency, serves as a learning facility that includes reading textbooks, expanding religious knowledge, and engaging in group study activities. The availability of a comfortable and conducive library environment enables students to manage their study time effectively. Students’ digital literacy skills support effective library utilization, allowing them to access, select, and comprehend information from digital sources independently. As a result, the library becomes an integral part of the learning process and the development of competencies in Al-Qur’an and Hadith. The optimization of the library through digital literacy has been proven to enhance the quality of learning and learning outcomes, as students can access various references, select relevant information, and understand the material more deeply. Moreover, digital literacy encourages independent learning and critical thinking skills, enabling students to connect new information with prior knowledge and thereby strengthen their understanding and mastery of Al-Qur’an and Hadith materials.